A comparative study of the subsoil in four different places in Maktab Polis Diraja Malaysia by using Atomic Absorption Spectroscopy h - Julia Haslini, Mat Jusoh (PPSP, Universiti Sains Malaysia, 2007)
Atomic absorption spectrometry (AAS) is being used for determining the metal ion concentration in soil sample. It is a common analytical method for trace or ultra trace (ppm or ppb level) determination. For this study AAS was used for analyzing the presence of metal ions in soil. This comparative study was done to show the difference in metal ion concentrations in soil samples collected in different points from an uphill at forensic laboratory, maktab PDRM in Cheras. The samples were collected in four different points and in four different depths, namely topsoil, soil from Y2 foot depth, soil from 1 foot depth, and soil from 1112 feet depth. In total sixteen samples were collected for AAS analysis. The purpose of this study is to compare the metal ion concentration in soil samples collected in different points and in different depths. The presence of metal ions in subsoil profile were compared and recorded. Eight metals have been chosen for comparison and their concentrations were compared. The chosen metals are K, Pb, Zn, Fe, Mg, Ca, Mn and Cu. Before using AAS examination preliminary examination of soil viz color, pH, particles size and presence any foreign material etc have been conducted. Then examination was done using AAS to obtain the metal ion concentrations present in the soil samples collected from different points and depths. The metal ions were extracted by using EDTA solution since it form complex as with metal ion present in soil samples resulting chelate formation. Then the solution was filtered and purified for AAS analysis. I found that all the metal ions concentration different and have this technique can be used for forensic soil analysis. It shows that no two samples from two different origins have the same metal ion concentrations.